Comparison of Tannin Levels in Brewed and Boiled Green Tea (Camellia Sinensis (L.) Kuntze) by UV-Vis Spectrophotometric Method - Styawan, Anita Agustina; Atun Yuliana (Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction: Green tea (Camellia sinensis (L.) Kuntze) has antibacterial and antioxidant properties that are effective in preventing and treating diseases. Green tea contains tannin compounds with antidiarrheal properties, stops bleeding and prevents inflammation of the oral mucosa. To get its properties, the way tea is processed affects the tannin content in tea. Aims: To determine the tannin content in brewed and boiled green tea using UV-Vis Spectrophotometric method. Method: The research method used was experimental research. The sample used was green tea taken from the cultivation site